15 YEARS OF “AFTER YOU DESSERT CAFÉ”, WHAT MAKES CUSTOMERS REPURCHASE: A QUANTITATIVE APPROACH - Chienwattanasook, Krisada; Sukjam, Sarocha; Chadee, Piyada; Lekhawichit, Nutnapha (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2023)
“After You”, a café that provides various desserts and beverages, has been in business since 2007, and recently become a public company. Thus, it is interesting to investigate personal factors, brand equity, and service marketing mix factors that influence customers repurchase decision. Questionnaires were used as the research instruments and passed the reliability test with coefficient above .80. Convenience sampling was employed, and the total sample size was 387 respondents who bought desserts and beverages from “After You”. To analyze the data, frequency, percentages, averages, and standard deviations, analysis of variance, and multiple regression were utilized. The study found that 1) personal factors including income influenced repurchase decision, 2) brand equity, including brand awareness and perceived quality of brand influenced the repurchase decision, and 3) service marketing factors, including personnel, promotion, service process, and price influenced repurchase decision with statistical significance at 0.05. Due to the image, quality of products, and services provided by After You, customers find the products of this dessert café worth paying. In addition, the marketing mix that focuses on employee service, service process, and physical environment that are more outstanding than other competitors lead “After You” to run the business more efficiently.